Αν $a=\dfrac{1}{x^{2}}+\dfrac{1}{y^{2}}$, $b=\dfrac{1}{x^{2}}-\dfrac{1}{y^{2}}$ τότε $\dfrac{a}{b}-\dfrac{b}{a}=\dfrac{4x^{2}y^{2}}{(y-x) (y+x)(x^{2}+y^{2})}$. O παρονομαστής του παρονομαστή μετά τις πράξεις γράφεται: $\dfrac{2(x^{2}+y^{2})(x-y)(x+y)}{x^{2}y^{2}}$ με τελικό αποτέλεσμα -1.
Αν $a=\dfrac{1}{x^{2}}+\dfrac{1}{y^{2}}$,
ΑπάντησηΔιαγραφή$b=\dfrac{1}{x^{2}}-\dfrac{1}{y^{2}}$ τότε
$\dfrac{a}{b}-\dfrac{b}{a}=\dfrac{4x^{2}y^{2}}{(y-x)
(y+x)(x^{2}+y^{2})}$.
O παρονομαστής του παρονομαστή μετά τις πράξεις γράφεται:
$\dfrac{2(x^{2}+y^{2})(x-y)(x+y)}{x^{2}y^{2}}$ με τελικό αποτέλεσμα -1.